2019
DOI: 10.1111/joor.12765
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergency department attendance of under 16‐year‐olds with dental problems

Abstract: Summary Background Medical emergency departments (MED) are under increasing pressure in the UK with suggestions that unnecessary attendances to MED, which may include dental problems, are to blame. Objectives The aim of this cross‐sectional study was to examine the period prevalence of under 16‐year‐olds attendance to medical emergency departments (MED) with oral and dental problems over a 5‐year period and investigate reason for attendance. This cross‐sectional study was carried out as part of a service evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(48 reference statements)
1
2
1
Order By: Relevance
“…The finding that children from more deprived areas more frequently access PEDs is in line with the existing literature. 4,13 Our findings also support the limited body of evidence that children attending the PED with TDIs are more likely to come from less deprived areas compared with children attending with NTDCs who are more likely to reside in more deprived areas. 14 Although it is known that children from more deprived areas suffer more preventable dental disease, 6 there has been limited research to explore the demographic of children attending with TDIs.…”
Section: Demographicssupporting
confidence: 77%
See 2 more Smart Citations
“…The finding that children from more deprived areas more frequently access PEDs is in line with the existing literature. 4,13 Our findings also support the limited body of evidence that children attending the PED with TDIs are more likely to come from less deprived areas compared with children attending with NTDCs who are more likely to reside in more deprived areas. 14 Although it is known that children from more deprived areas suffer more preventable dental disease, 6 there has been limited research to explore the demographic of children attending with TDIs.…”
Section: Demographicssupporting
confidence: 77%
“…The combined number of dental attendances at the units observed within a 1-year period was 667. This figure is proportionally higher than the 868 attendances over a 5-year period in a comparative study in Newcastle, UK, which included maxillofacial and oro-mucosal conditions 13 and proportionately lower than the 687 attendances observed in Sheffield, UK, in 2012-2013, given that our data are derived from two sites. 14 Additionally, we found that NTDCs accounted for 64.9% of all dental attendances, which contrasts existing evidence that TDI is the most common cause for presentation.…”
Section: Demographicscontrasting
confidence: 58%
See 1 more Smart Citation
“…Alternatively, some patients with TDIs may present to a hospital Accident and Emergency department. A recent north‐east England study reported that the most common dental reason for attendance in 6‐ to 11‐year‐olds was dental trauma 8 . Thus, the provision and delivery of care for patients with TDIs can be disjointed.…”
Section: Introductionmentioning
confidence: 99%